Impact of Battery Rating on Performance of Rooftop PV Supporting Household Loads, Regualting PCC Voltage and Providing Constant Output Power to Grid - Jabalameli, Nasim; Masoum, Mohammad Sherkat; Shahnia, Farhad; Hosseini Mehr, Tahoura (University of Tasmania, 2013)
The dependency rooftop photovoltaic generation system (rooftop PV) output power to environmental factors (sun radiation, panel temperature, passing clouds, etc.) and loading level (operating point on v-i characteristics) may result in sudden output power variations particularly during cloudy periods. This paper will first implement a rooftop PV with a battery storage energy management strategy (BS-EMS) to support the household loads and regulate the voltage at point of common coupling (PCC) while providing the grid with a constant output power during daylight. System operation is based on the power balance between rooftop PV, BS and grid which is achieved by dynamic control of the BS converter to assure constant output power to the grid during daylight. Then, the impact of battery rating on the performance of BS-EMS will be investigated for typical sunny and cloudy days in summer and winter.